If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -11 + -4y + 8 = 0 Reorder the terms: -11 + 8 + 9y + -4y = 0 Combine like terms: -11 + 8 = -3 -3 + 9y + -4y = 0 Combine like terms: 9y + -4y = 5y -3 + 5y = 0 Solving -3 + 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5y = 0 + 3 5y = 0 + 3 Combine like terms: 0 + 3 = 3 5y = 3 Divide each side by '5'. y = 0.6 Simplifying y = 0.6
| 6(3+4x)=-3 | | -3(x-5)=2(-2x-6)+6 | | 3(9+7x)=27 | | x=-9(.5)-1 | | 3(7-6x)=21 | | 140n^2=-36nZ+8 | | -3(4+6x)=-48 | | x+9y=-1 | | --3(4r-8)=-36 | | -2X+3X=-25 | | -8x-6=3x+27 | | 6(9+2x)=78 | | 7y-(3y+12)=8-(5y-2) | | 6(-2x-8)=-48 | | -62+11y+6=5(3-5)-7 | | 4ab^2/-20a^3b | | -15n+18=-13n-12 | | 7(3x+4)=-14 | | 6(3x+5)=-24 | | 5x+10=7x+26 | | 8-18=z/-7= | | 3=xx+3-5x | | 2v+17=47 | | w-144=-11 | | 2x+1=3+x | | 3x-21y=-24 | | y-(-99)=4 | | 5x+9=-3+7x | | 6.5x-3=11 | | 1-6x=5x+1 | | k-7=-12 | | -2(-2-4n)-4n=-2+5(n+3) |